Ensaios sobre Investimento Direto Estrangeiro: determinantes e efeitos sobre a indústria brasileira - Silva, Janaína Cabral da (2020)
This thesis is divided into three Essays, whose general objective is to identify the main determinants of Foreign Direct Investment (FDI) and the effects of this investment on productive efficiency in selected sectors of Brazilian industry. In Essay I, a systematic review is carried out, through the application of the Meta-Regression Analysis (MRA) technique, to synthesize literary evidence that seeks to detect the main determinants of the attraction of FDI in recipient countries and evaluate how the different strategies empirical data, applied in the developed researches, can influence the results of the researchers' studies. For the selection of studies, a keyword search algorithm was used in the research database of ScienceDirect. After applying the criteria established for the MRA, a total of 1,154 observations were obtained, derived from 16 scientific studies published and indexed in the international database between the years 2009 and 2019. The evidence found suggests that the impact of the factors considered determinants of the FDI in the literature depends on the various empirical strategies adopted by the researcher, the variables used and the space for analysis. In order to detect the main determinants of the FDI decision process by the economic agents in the Brazilian industry, Essay II adopted as an empirical analysis strategy the GLM (Generalized Linear Models) estimation technique with data referring to the years 2007 to 2017. Data were collected from institutions such as IBGE, BACEN, among others. The results found allow us to identify that the salaries and wages of the industrial activity sector and the value of industrial transformation have a positive relationship with the volume of FDI attracted to industrial economic activities in Brazil over the analysis period. In Essay III, the effects caused by the FDI flows received on the level of productive efficiency of industrial economic activities are examined, made possible through the application of a quantitative two-stage approach. The first stage assesses the relative productivity of the industrial activities considered using the DEA-CCR Data Envelopment Analysis technique. Then, the productive efficiency indicator calculated as a dependent variable in the econometric approach used is applied, whose Tobit estimation technique constitutes a reference model for measuring the impact of FDI on Brazilian industrial productivity. Additionally, the impact that FDI can have on labor productivity is measured empirically in two ways: (i) the ratio between the Value of Industrial Transformation (VTI) and the number of Employed Personnel (PO) of Brazilian industrial activities and; (ii) the ratio between Net Sales Revenue (RLV) and the PO of industrial activities. It is observed that the received FDI tends to positively affect the level of industrial productivity in all measures used.